Eco-tourism and Associate Lives across Tharu-inhabited Region of India-Nepal Border - Dangaura, Mohan (Literary Studies, 2025)
This paper explores the potential for developing the Tharu-inhabited region along the India-Nepal border, specifically focusing on the Farwestern region of Nepal and the Uttar Pradesh and Uttarakhand regions of India. The areas of Kailali, Kanchanpur, Bardia, and Banke in the Far-Western and Lumbini States are connected to India through various wildlife reserves, including the Kishanpur Wildlife Sanctuary, Pilibhit Tiger Reserve, Dudhwa Tiger Reserve, and Katerniyaghat Wildlife Sanctuary. The Tharu communities residing in these border areas share many similarities in terms of language, dress, food, houses, and cultural practices. Despite being separated by rivers and jungles rather than concrete boundaries, these shared cultural aspects make the Tharu-populated border region an ideal location for the development of a biological corridor and international eco-tourism hub. However, despite some local efforts to develop the villages into homestays and promote cultural exchange between the two countries, there is a lack of support and promotion from both social organizations and the government. Additionally, it has been observed that the Tharus in Nepal often receive fewer government allowances, development schemes, and programs for upliftment compared to their counterparts across the border. As a result, many Tharus from Nepal migrate to India in search of employment, career opportunities, and better education policies. Despite occasional political tensions between the two countries, the Tharu communities on both sides of the border have maintained a harmonious relationship and have provided each other with support and brotherly sentiments. Given the immense potential for eco-tourism in this region, it is crucial for the government and social organizations to provide the necessary assistance and support to facilitate its development.